The aerodynamic derivatives of an aerofoil oscillating in an infinite staggered cascade - Craven, A. H. (College of Aeronautics, 1960)
Thin aerofoil theory is used to obtain, in integral form the aerodynamic derivatives of an aerofoil oscillating in an infinite cascade. The theory allows for arbitrary stagger angle and phase difference between adjacent blades of the cascade. The expressions obtained reduce, for zero stagger and for in phase and antiphase oscillations, to known results.